Montessori modeli ile din ve değerler eğitimi (İstanbul örneği) - Olcaytuberdi, Nurşen (My University, 2019)
Alternatif eğitim modellerinden Montesori modelini din eğitimi açısından incelediğimiz araştırmamızın temel problemi, bu modelin din ve değerler eğitiminde uygulanmasının imkanıdır. Bu kapsamda çalışmamızda Montessori modelinin ne olduğu, çocuğa ve eğitimciye yaklaşımı, Montessori modelinin Türkiye'deki durumu, din ve değerler eğitimine bakışının nasıl olduğu gibi hususlar incelenmiştir. Bu inceleme sonucu Montesori modelinde öne çıkan insanın doğası, özgürlük ve tecrübe kavramları din eğitimi açısından ele alınmıştır.İstanbul'da bulunan dört Montessori okulunun müdürü, din ve değerler eğitimi öğretmenleri ile mülakatlar gerçekleştirilmiştir. Mülakat verileri doğrultusunda Montessori modeli ile din ve değerler eğitiminin imkanı değerlendirilmiştir.

The main aim of our research is to discuss that if Montesori model could be an alternative model for religious education or not and the possibility of applying this model in the education of religion and values in terms of Islam. In this context, firstly we want to examine Montessori model, its approach of children and educators.As second part of the study, as important subjects of the model, the nature of human being, concepts of freedom and experience are discussed in terms of religious education.In the third chapter, we discussed results of interviews with the heads of four Montessori schools in Istanbul, teachers of religion and values education. Considering the data of the interviews, the possibility of religious and values education with the model in terms of Islam is examined.
Keywords: Din eğitimi; Felsefe ve din; Montessori; Montessori Religion Education; Philosophy and religion; Religious education